Acyclic Nucleoside Phosphonates Containing 9-Deazahypoxanthine and a Five-Membered Heterocycle as Selective Inhibitors of Plasmodial 6-Oxopurine Phosphoribosyltransferases - Kaiser, Martin Maxmilian; Baszczyňski, Ondřej; Hocková, Dana; Poštová-Slavětínská, Lenka; Dračínský, Martin; Keough, Dianne T; Guddat, Luke W; Janeba, Zlatko (ChemMedChem, 2017)
Acyclic nucleoside phosphonates (ANPs) are an important class of therapeutic drugs that act as antiviral agents by inhibiting viral DNA polymerases and reverse transcriptases. ANPs containing a 6-oxopurine unit instead of a 6-aminopurine or pyrimidine base are inhibitors of the purine salvage enzyme, hypoxanthine-guanine-[xanthine] phosphoribosyltransferase (HG[X]PRT). Such compounds, and their prodrugs, are able to arrest the growth of Plasmodium falciparum (Pf) in cell culture. A new series of ANPs were synthesized and tested as inhibitors of human HGPRT, PfHGXPRT, and Plasmodium vivax (Pv) HGPRT. The novelty of these compounds is that they contain a five-membered heterocycle (imidazoline, imidazole, or triazole) inserted between the acyclic linker(s) and the nucleobase, namely, 9-deazahypoxanthine. Five of the compounds were found to be micromolar inhibitors of PfHGXPRT and PvHGPRT, but no inhibition of human HGPRT was observed under the same assay conditions. This demonstrates selectivity of these types of compounds for the two parasitic enzymes compared to the human counterpart and confirms the importance of the chemical nature of the acyclic moiety in conferring affinity/selectivity for these three enzymes.
Keywords: pentosyltransferasy; vztahy mezi strukturou a aktivitou; Models, Molecular; nukleosidy; organofosfonáty; hypoxanthiny; Humans; Antimalarials; antimalarika; Organophosphonates; Hypoxanthine Phosphoribosyltransferase; inhibitors; phosphonates; Hypoxanthines; hypoxanthinfosforibosyltransferasa; Plasmodium vivax; Nucleosides; Pentosyltransferases; malaria; lidé; molekulární modely; purine salvage; nucleosides; Structure-Activity Relationship; Plasmodium falciparum